Multipotential Alkaline Protease From a Novel Pyxidicoccus sp. 252: Ecofriendly Replacement to Various Chemical Processes - Sharma, Sonia; Kumar, Shiv; Kaur, Rajinder; Kaur, Ramandeep (Frontiers in Microbiology, 2021)
A newly isolated alkaline protease producing myxobacterium was isolated from soil. The strain was identified as Pyxidicoccus sp. S252 on the basis of 16S rRNA sequence analysis. The extracellular alkaline proteases produced by S252 (PyCP) was optimally active in the pH range of 11.0 to 12.0 and temperature range of 40°C to 50°C The zymogram of PyCP showed six caseinolytic protease bands. The proteases were stable in the pH range of 8.0 to 10.0 and temperature range of 40°C to 50°C. The activity of PyCP was enhanced in the presence of Na+, Mg2+, Cu2+, Tween-20 and H2O2, whereas in Triton X-100, glycerol, ethylenediaminetetraacetic acid (EDTA) and Co2+, it was stable. PyCP showed potential in various applications. The addition of PyCP in the commercial detergent enhanced the wash performance of the detergent by efficiently removing the stains of tomato ketchup and coffee. PyCP efficiently hydrolyzed the gelatin layer on X-ray film to release the embedded silver. PyCP also showed potent dehairing of goat skin and also efficiently deproteinized sea shell waste indicating its application in chitin extraction. Thus, the results of the present study indicate that Pyxidicoccus sp. S252 proteases have the potential to be used as an eco-friendly replacement of chemicals in several industrial processes.